Utilization of Waste Materials Rubberwood Bottom Ash in the Production of Hollow Non-Load-Bearing Concrete Masonry Unit - Thongkhwan, Thaweesak; Kuasakul, Tavorn; Laksanakit, Chuthamat; Chusilp, Nuntachai; Tabyang, Wisitsak; Lukjan, Arun; Sookmanee, Pongsak; Chumprom, Premmanat (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This study aims to evaluate the feasibility of using rubberwood bottom ash (RWBA) as an aggregate in the production of non-load-bearing hollow concrete blocks. The investigation involves replacing 25 % and 50 % by weight of stone dust with rubberwood bottom ash. Five mixtures of hydraulic cement to aggregate by weight were tested: 1:6, 1:7, 1:8, 1:9, and 1:10. Each mixture was further analyzed at three different water-to-cement (W/C) ratios: 0.50, 0.60, and 0.70, resulting in a total of 45 mixtures. Mixtures at 28-days curing age with average compressive strength exceeding 4.14 MPa were selected for the production of hollow concrete blocks. These blocks were subsequently tested for compliance with the Thai Industrial Standard TIS 58-2560, assessing density, water absorption, average compressive strength, and thermal conductivity. The results revealed that only five mixtures met the standard criteria: Mix ratio 1:6 with 75 % stone dust and 25 % RWBA at W/C ratios of 0.6 and 0.7, Mix ratio 1:6 with equal proportions (50 %) of stone dust and RWBA at a W/C ratio of 0.7, and Mix ratio 1:7 with 75 % stone dust and 25 % RWBA at W/C ratios of 0.6 and 0.7. Among these, the optimal mixture was identified as the mix ratio 1:6 with 50 % stone dust and 50 % RWBA at a W/C ratio of 0.7. This mixture not only allowed for the highest replacement rate of RWBA (50 %) but also exhibited the lowest thermal conductivity at 0.863 W/m·K. The findings indicate a high potential for utilizing rubberwood bottom ash as a partial replacement for fine aggregates in the production of non-load-bearing hollow concrete blocks. This approach contributes to the development of environmentally friendly construction materials.